IMPLIKASI PENDIDIKAN AGAMA ISLAM DALAM KELUARGA TERHADAP KETERAMPILAN MEMBACA AL-QUR’AN PADA ANAK (Study kasus Taman Pendidikan Al-Qur’an darul Muttaqin Klantingsari Tarik sidoarjo - abdul hamid ma'rufi; Ahmad Baidowi; Mohammad Fahrudi Noer (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2025)
ABSTRACT This research addresses the issue of how the implementation of Qur'an reading is carried out for children at Taman Pendidikan Al-Qur’an (TPA) Darul Muttaqin, Klantingsari, Tarik, Sidoarjo, and how parents make efforts toward their children’s education in Qur'an reading skills. The aim is to understand and explain how the practice and implications of Islamic religious education are implemented for children at TPA Darul Muttaqin Klantingsari Tarik Sidoarjo. The objective of this research is to identify the efforts made by families in the implementation of Islamic religious education regarding Qur'an reading skills in children at TPA Darul Muttaqin Klantingsari Tarik Sidoarjo. It seeks to understand what efforts are made by families in carrying out Islamic education for their children. The research method used in this study is field research to obtain primary data, and also descriptive qualitative research methods. The subjects of this study are parents and children. The data collection techniques used include observation, interviews, and documentation. Conclusion of the research results: Parental responsibility for their children’s education in Qur'an reading skills at TPA Darul Muttaqin Klantingsari Tarik Sidoarjo is categorized as quite optimal. This is seen in how parents educate, nurture, and raise their children with love, providing understanding and knowledge about religion—particularly in Qur’an reading skills. They also provide lawful sustenance and pray for their children's well-being. The efforts made by parents regarding their children's education in Qur’an reading at TPA Darul Muttaqin Klantingsari Tarik Sidoarjo are considered quite maximal. Parents try to provide motivation and guidance, such as giving rewards, accompanying their children, and applying discipline when necessary. Parents do not solely hand over the responsibility of teaching Qur’an reading skills to the religious teachers.